Quisarctus yasumurai gen. et sp. nov. (Arthrotardigrada: Halechiniscidae) from a submarine cave, off Iejima, Ryukyu Islands, Japan - Fujimoto, Shinta (Zootaxa, 2015)
Quisarctus yasumurai gen. et sp. nov. (Arthrotardigrada: Halechiniscidae) is described from the submarine cave ‘Daidokutsu’, off Iejima, Okinawa Islands, Ryukyu Islands, Japan. It is characterised by a cylindrical body, long primary clava and shorter lateral cirrus inserted on a common cirrophore, and simple digits of unequal lengths (without folds, peduncles, proximal pads, pretarsi, or wrinkles) that terminate in a sheathed, small, crescent-shaped claw with a minute calcar. Quisarctinae subfam. nov. is erected for this unique new genus.